2019
DOI: 10.7150/jca.32806
|View full text |Cite
|
Sign up to set email alerts
|

STING signaling is a potential immunotherapeutic target in colorectal cancer

Abstract: Background: Stimulator of Interferon Genes (STING) is an innate immune sensor for cytosolic DNA. STING signaling activation is indispensable for type I interferon response and the anti-cancer immune response by CD8 + T cells. The aim of this study was to characterize intratumoral STING expression pattern and its clinical implication in colorectal cancer (CRC). Methods: We analyzed STING and CD8 expression in 225 CRC patients who underwent surgical resection. Clinicopathological variables and survival outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 30 publications
5
66
0
Order By: Relevance
“…15 16 Over the past decade, cancer immunotherapy has emerged as a potent and effective therapeutic strategy for advanced cancers. [17][18][19][20]…”
Section: Introductionmentioning
confidence: 99%
“…15 16 Over the past decade, cancer immunotherapy has emerged as a potent and effective therapeutic strategy for advanced cancers. [17][18][19][20]…”
Section: Introductionmentioning
confidence: 99%
“…Recently studies demonstrated that STING pathway had tremendous potential for immunotherapy from bench to bedside (24,(45)(46)(47). However, whether STING pathway involved in neuropathic pain process and whether STING pathway regulate ER-phagy process still remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…STING serves as an ER adaptor, being required in elevated ER stress condition (22). Its conformational changes and phosphorylation result in its translocation from ER to distinct perinuclear endosomes near Golgi (20,23,24). STING phosphorylation induces TANK binding kinase 1 (TBK1) phosphorylation and subsequently leads to the phosphorylation of interferon regulatory factor3 (IRF3) production (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…STING pathway activation was reported to inhibit colorectal tumorigenesis and could be a potential immunotherapeutic target in human colorectal cancer (21). Meanwhile, irinotecan, the prodrug of SN38, is clinically used to treat colon cancer.…”
Section: Ps3d1@dmxaa Shows Potent Therapeutic Effects In Different Mumentioning
confidence: 99%